Estudo comparativo sobre dois detectores planares e um volumétrico para o comissionamento de filtros dinâmicos de aceleradores lineares clínicos - Araujo, Andreyson da Silva (2018)
In radiation therapy, the lack of homogeneity of the planned volume of treatment dose can be compensated by using physical or dynamic wedges. Dynamic wedges were introduced to overcome, above all, the angulation limitations of physical wedges. But for dynamic wedges to be implemented in the radiotherapy routine, they need to undergo dosimetry and quality control procedures. For this, in addition to the cylindrical ionization chambers conventionally employed in radiotherapy beam dosimetry, there are more modern detectors that allow mapping in two or three dimensions the doses deposited by these beams. The objective of this work was to evaluate the efficiency of two planar detectors (MatriXX e QA BeamChecker Plus), and a volumetric (ArcCHECK) in the commissioning of dynamic wedges, discussing the advantages and disadvantages of one detector in relation to the others. A cylindrical ionization chamber was used to determine the percentage depth dose and the dose absorbed in water. The data obtained with the ionization chamber were compared with those defined by treatment planning system (TPS). MatriXX efficiency was investigated in tests of symmetry of collimators, linearity of dose, dose rate, filter factor, dose profiles in different depths to dynamic wedges of 30, 45 and 60º, and dose distribution analysis. ArcCHECK efficiency was verified in the test of the influence of gravitational force on the collimators, simulating filters 30, 45 and 60º. For QA BeamChecker Plus, the efficiency was analysed in the beam constancy test using dynamic wedges of 30, 45 and 60°. In all the efficiency tests, these three detectors presented good results, being suitable for the commissioning of the dynamic wedges.